The comparison effect between pure caffeine and regular coffee on attention performance among university students / Masshera Jamaludin ... [et al.] - Jamaludin, Masshera; Shariff, Muhamad Amin; Ismail, Zulkifli; Mohd Aznan, Ellail Ain; Miswan, Mohamad Syafiq (2021)
Caffeine is the most consumed beverage worldwide; it has been revealed to produce several effects on human health including the effect on attention performance. A previous study indicated that most people consumed caffeine to enhance alertness and increase overall performance at some stage in mentally and physically intensive situations. The purpose of this study was to compare the effect of pure caffeine (PC) and regular coffee (RC) ingestion on attention performance among local university students. Thirty UiTM Perlis students with low or non-caffeine consumers (aged 20-22 years) were involved in this study. Each group consumed 220 mL of designated caffeine beverages. The study utilized a single-blinded and randomized group. The attention performance was measured at the baseline and experimental trial using the Mackworth Clock Test (MCT). The result showed there was no significant main effect for time with attention score between baseline and experimental trial for both groups. However, a significant main effect between groups was reported on attention performance, F (1, 28) = 7.652, p = .010. Additionally, the RC group has shown a greater improvement from the baseline (9.8±3.5) to the experimental trial (8.3±3.4) compared to the PC group (baseline=6.9±4; experimental=5.7±2) toward attention performance. This study demonstrated that in healthy university students, the administration of regular caffeine beverages elicited a little enhancement of attention performance. Thus, a need for further study should be done on the physiological and psychological effects to examine the mechanism of the caffeine ingested.